Pengaruh Current Ratio (CR), Cash Conversion Cycle (CCC), dan Perputaran Aset (Total Asset Turnover), Terhadap Investasi Modal (Capital Expenditure - CAPEX) Pada Perusahaan-Perusahaan Sektor Infrastruktur Yang Terdaftar di Bursa Efek Indonesia Selama Periode Tahun 2018-2024 - Afandi, M Akbar Dwi; Putri Azzahra; Izdtihar, Shofiah Thoyyibatul; Ahmad Muzaky; Syabani, Farhan Abung; Rifkhan Rifkhan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. This study aims to examine the effect of the Current Ratio (CR), Cash Conversion Cycle (CCC), and Total Asset Turnover on Capital Expenditure (CAPEX) in infrastructure sector companies listed on the Indonesia Stock Exchange during the 2018–2024 period. The study employs a quantitative approach using panel data regression, with samples selected through purposive sampling and data obtained from companies’ annual financial statements. The estimation is conducted using the Random Effect Model with a Generalized Least Squares approach, which is considered appropriate for capturing differences in firm characteristics as well as changes over time. The results indicate that, simultaneously, CR, CCC, and Total Asset Turnover do not have a significant effect on CAPEX. The partial test results also show that each independent variable does not significantly influence corporate capital expenditure decisions. These findings suggest that capital investment decisions in infrastructure companies are not solely driven by internal financial conditions such as liquidity, working capital efficiency, and asset utilization. Instead, capital expenditure is more strongly influenced by external factors, including long-term financing structures, government policies, and the capital-intensive and long-term nature of infrastructure projects Keywords: Capital Expenditure, Current Ratio, Cash Conversion Cycle, Total Asset Turnover, Infrastructure